MANAGEMENT OF THE PSEUDOBULBAR AFFECT (PBA) IN KABUKI SYNDROME COMBINED DEXTROMETHORPHAN-FLUOXETINE TREATMENT AS AN ALTERNATIVE TO DEXTROMETHORPHAN/QUINIDINE - Cordova, Victor Hugo; Goldani, André; Belmonte-de-Abreu, Paulo (Clinical and Biomedical Research, 2021)
A case report of a patient with pseudo bulbar affect previous treatments included haloperidol (10mg), Inosina pranobex (600mg), clozapine (600mg), olanzapine (20mg), carbamazepine (200mg), paroxetine (20mg), phenobarbital (100mg) and topiramate (50mg), all suspended at August 2016, with current use of quetiapine (700mg) Chlorpromazine (600mg) (+ 200mg on demand of aggression), clonazepam (4 mg), valproate 2500 mg, propranolol (40mg). that was successful treated with off label treatment (dextromethorphan plus quinidine). Previous Brief Psychiatric Rating Scale and Clinical Global ImpressionImprovement was applied after and before treatment with dextromethorphan (20mg) plus fluoxetine (20 mg, further increased to 40 mg). Previous Brief Psychiatric Rating Scale BPRS score 56 points and Clinical Global Impression-Severity (CGI-S) Score was 6 (severely ill). The addition of dextromethorphan (20mg) and fluoxetine (20 mg, further increased to 40 mg), allowed clear improvement of pathological crying and outbursts, with BPRS decrease of 8 points and Clinical Global Impression-Improvement (CGI-I) 2 (much improved) – especially pertaining to PBA related symptoms and aggressive behavior. There were no noticeable side-effects. This case report shown an interesting clinical response. It’s could be a great alternative in treatment of pseudobulbar affect symptoms. Even though an only case and a great clinical study be necessary.